2014
DOI: 10.1038/sj.bdj.2013.1234
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dental team in promoting health equity

Abstract: This paper highlights practical ways that the primary care dental team can promote oral health equity for their patients and their wider community. The NHS is going through yet another period of major structural, organisational and policy change. In England, a totally new commissioning and organisational landscape has been created with the formation of NHS England. A unique opportunity now exists to integrate action on tackling both oral and general health inequalities. The time for this action is now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 10 publications
0
33
0
4
Order By: Relevance
“…La organización de programas y servicios debe partir de que existe suficiente investigación que soportan el control de la enfermedad, siempre y cuando se establezcan las medidas necesarias para detectarla a tiempo y controlar su progresión de manera eficaz, a la luz de los conceptos actuales de tratamientos no invasivos [20,27,28]; pero se requiere tener en consideración las realidades de los grupos con menores ingresos, incluyendo sus experiencias en relación con los sistemas de atención odontológica [29].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La organización de programas y servicios debe partir de que existe suficiente investigación que soportan el control de la enfermedad, siempre y cuando se establezcan las medidas necesarias para detectarla a tiempo y controlar su progresión de manera eficaz, a la luz de los conceptos actuales de tratamientos no invasivos [20,27,28]; pero se requiere tener en consideración las realidades de los grupos con menores ingresos, incluyendo sus experiencias en relación con los sistemas de atención odontológica [29].…”
Section: Discussionunclassified
“…La enfermedad representa un reto mayor en los primeros seis años de vida [30] y, por tanto, debe ser abordada mediante nuevos enfoques. Para este propósito se requiere reconocer la influencia de otros aspectos sociales, económicos y políticos, e involucrar estrategias colaborativas con otros profesionales de la salud y la educación, de manera que se favorezca el acceso a prácticas de cuidado rutinarias, que han mostrado ser efectivas en tanto involucran esfuerzos conjuntos [29,30,31].…”
Section: Discussionunclassified
“…Un reto para una ciudad que ha sido líder en salud bucal es integrar acciones intersectoriales que promuevan el desarrollo de niños y niñas, a través del acompañamiento y del cuidado, en estrategias que superen los enfoques tradicionales morbicéntricos y trabajen de la mano con los equipos de salud, para materializar los principios de la política pública en salud bucal: equidad, universalidad, integralidad, accesibilidad, disponibilidad, aceptabilidad y gestión participativa que contribuyan a cerrar la brecha de inequidades en salud bucal, reflejo de otras brechas sociales [29].…”
Section: Discusión Y Conclusionesunclassified
“…This was also observed in studies which evaluated changes in the OHRQoL of children after a short-term dental caries treatment 12,15,17,29 and corroborates the importance of the promotion of equal access to dental care and quality of treatment outcomes to reduce inequalities in oral health. 31 The 1-year follow-up in the DTG demonstrated that the scores of all CPQ 8-10 domains continued to improve and were statistically different from those at baseline, except for the OS domain. This result can be due to the fact that, at this age, children have mixed dentition (age 8 to 12 years), which can make them experience problems related to natural processes, such as exfoliation of deciduous teeth, dental eruption, or interdental spaces because of an unerupted permanent teeth.…”
Section: Discussionmentioning
confidence: 88%